Modulation of intracortical circuits in primary motor cortex during automatic action tendencies - Xue Xia; Yansong Li; Yuyu Song; Yuanjun Dong; Robert Chen; Jian Zhang; Xiaoying Tan (Brain Structure and Function, 2024)
Humans display automatic action tendencies toward emotional stimuli, showing faster automatic behavior (i.e., approaching a positive stimulus and avoiding a negative stimulus) than regulated behavior (i.e., avoiding a positive stimulus and approaching a negative stimulus). Previous studies have shown that the primary motor cortex is involved in the processing of automatic actions, with higher motor evoked potential amplitudes during automatic behavior elicited by single-pulse transcranial magnetic stimulation. However, it is unknown how intracortical circuits are involved with automatic action tendencies. Here, we measured short-interval intracortical inhibition and intracortical facilitation within the primary motor cortex by using paired-pulse transcranial magnetic stimulation protocols during a manikin task, which has been widely used to explore approaching and avoiding behavior. Results showed that intracortical facilitation was stronger during automatic behavior than during regulated behavior. Moreover, there was a significant negative correlation between reaction times and intracortical facilitation effect during automatic behavior: individuals with short reaction times had stronger faciliatory activity, as shown by higher intracortical facilitation. By contrast, no significant difference was found for short-interval intracortical inhibition between automatic behavior and regulated behavior. The results indicated that the intracortical facilitation circuit, mediated by excitatory glutamatergic neurons, in the primary motor cortex, plays an important role in mediating automatic action tendencies. This finding further supports the link between emotional perception and the action system.

Different changes in pre- and postsynaptic components in the hippocampal CA1 subfield after transient global cerebral ischemia - Yan Zhang; Bai-Hong Tan; Shuang Wu; Cheng-Hao Wu; Jia-Le Suo; Yue Gui; Cheng-Mei Zhou; Yan-Chao Li (Brain Structure and Function, 2022)

Reconfiguration patterns of large-scale brain networks in motor imagery - Tao Zhang; Fei Wang; Mengchen Li; Fali Li; Ying Tan; Yangsong Zhang; Hang Yang; Bharat Biswal; Dezhong Yao; Peng Xu (Brain Structure and Function, 2019)